Engagement in Computer Science and IT -- What! A Matter of Identity? - Peters, A-K; Pears, A. (2013 Learning and Teaching in Computing and Engineering (LaTiCE), 2013)
In this paper, we develop and illustrate the use of a new theoretical framework to systematically investigate the development of student identity in Computer Science and IT. Identity has been identified as a critical issue in the endeavour to increase students' engagement in Computer Science and related areas. Findings from earlier studies indicate that students' doubts about future engagement are often due to an unfortunate perception of the discipline, that it lacks meaning, which leads to a tendency to dissociate themselves from IT and Computer Science as an area of further study. To understand different ways of experiencing engagement in the discipline as personally meaningful, we have integrated aspects of Lave and Wenger's social theory of learning, especially Wenger's notion of meaning, with a model developed by Entwistle that describes how conceptions of learning and knowledge expand and evolve in the context of the educational experience. We explore the use of this theoretical framework on reflections that we collected from all novice students of the Computer Science and IT engineering programme at Uppsala University, in which the students reflect on their choice of study program, goals, and expectations for education. The theoretical framework is furthermore discussed with respect to our broader research project to study students' identity development in Computer Science and IT as well as the role of education, how it supports or hinders students and how this can be used to inform educational development.